Children's work in family and community contexts: Examples from Young Lives Ethiopia - Pankhurst, A; Crivello, G; Tiumelissan, A (Young Lives, 2016)
In this paper we present findings on the place of work in the lives of children. These findings come from a study carried out with children in three Ethiopian communities, in two cities and one rural area. We describe the types of work done by boys and girls of different ages, and show how these children seek to combine work with school. We find that, with changes in the economic contexts, some children started paid work as early as 8 years old but that most younger children were mainly involved in work for the household. Gender differences become more prominent with age: compared to boys, older girls routinely take on greater responsibility for household chores and care activities; going to school or undertaking paid work does not diminish their household responsibilities. Based on the findings we suggest that social protection policies and programmes should provide insurance against community and household shocks and support children in affected households. Flexible learning arrangements can enable children who are working to continue with schooling.